Characteristics of Tuna Sausage with The Addition of Yellow Pumpkin Flour as a Source of Protein and Vitamin A in COVID-19 Pandemic - Amalia, Mutia Reski; Sugiyanto, Maya Kumalasari; Umar, Pepi Sugianto; Hadi, Novian Swasono (Universitas Airlangga, 2023)
Enhancing immunity is crucial against COVID-19, achieved through improved nutrition, especially protein and vitamin A. Protein aids in antibody production, which is vital for infection defence. Malnourished children have weakened immunity due to inadequate antibody formation, leading to higher mortality rates. Vitamin A also bolsters immunity. This study focused on tuna sausages enriched with pumpkin flour to enhance nutritional value and visual appeal. The aim was to boost agricultural and fisheries productivity for food security during the pandemic, offering a healthy, cost-effective protein and vitamin A source from local resources. The study assessed the characteristics of these sausages through a randomized design with three formulations: 10%, 20%, and 30% pumpkin flour. Nutritional analysis was conducted using the proximate method. Results favoured the second formula, showing significant differences in taste, colour, and texture. The third formula had the highest protein content, while the second one excelled in fat and vitamin A.